The God in Me: Faith, Reality TV, and Black Women - Egwu, Chetachi A. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The display of spirituality, faith and religion is not a new phenomenon among black women in the United States, nor is it new to the world of media. Africans came to the Americas with their own sense of spirituality and religion, and the awareness of a higher being became the mortar that bound the community together during the trials of enslavement and subsequent oppression. Not surprisingly, this legacy of worship continues to provide solace and strength, with black women at the helm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)